Complete Video-Assisted Thoracoscopic Surgery and Traditional Open Surgery for Elderly Patients With NSCLC - Mao, Yi; Gao, Zhaojia; Yin, Yajun (Frontiers in Surgery, 2022)
Objective: To observe the efficacy of complete video-assisted thoracoscopic surgery (CVATS) and traditional open surgery (TOS) in the treatment of elderly patients with non-small cell lung cancer (NSCLC) and the effects on cardiopulmonary function. Methods: Total of 120 elderly patients with primary NSCLC who were treated surgically in our hospital from January 2018 to January 2021 were selected and divided into the study group and the control group according to the different surgical procedures, 60 patients in each group. CVATS was adopted in the research group and TOS was adopted in the control group. The operation indexes and cardiopulmonary function indexes of the two groups were observed and compared. The serum C-reactive protein (CRP) level and visual analogue scale's (VAS) score of the patients at different time points were detected. To observe the incidence of postoperative complications in patients. Results: The perioperative indexes such as operation time were significantly different between the two groups (P<0.05), but the number of lymph node dissection was not significantly different (P>0.05). The serum CRP level and VAS score of the observation group were significantly lower than those of the control group on the 1st 3rd and 7th postoperative days (P<0.05). There were significant differences in cardiopulmonary function between the two groups on the 7th postoperative days (P<0.05). The incidence of adverse reactions in the observation group was significantly lower than that in the control group (P>0.05). Conclusion: CVATS has reliable curative effect in the treatment of NSCLC. Compared with TOS therapy, CVATS has less impairment of cardiopulmonary function and fewer complications, which is beneficial to the recovery of elderly patients. It is a safe and reliable scheme for the treatment of elderly patients with NSCLC.